Asymmetric beam-beam effect study in a highly polarized electron-ion collider - Ming Xuan Chang; Jian Cheng Yang; Lei Wang; Jie Liu; He Zhao; Guo Dong Shen; Hang Ren; Yun Zhe Gao; Qi Yu Kong; Fu Ma; Min Xiang Li (Physical Review Accelerators and Beams, 2023)
The EicC (The highly polarized Electron-ion collider in China) project proposes a scheme with different numbers of bunches in the two rings, which leads to an asymmetric beam-beam effect, also known as the gear-change effect. In order to investigate the feasibility of asymmetric collision in EicC, a self-consistent simulation program named athenagpu, which uses GPU for high-performance computing, was developed. A linearized matrix model is used to account for the dipole instability that occurs in the simulation. The simulation results in different collision modes show that asymmetric collision can lead to instability, and the beam can be stabilized by adjusting the nominal tunes. In the process of scanning the beam intensity, instability may occur as the beam intensity decreases, and this instability can be suppressed by compensating the nominal tunes. Offset collision simulations show that the decoherence time of the displaced bunch is shorter in the asymmetric collision than in the symmetric collision. The study in this paper suggests that asymmetric collision is promising for EicC when only the beam-beam effect is considered.